Epidemiologic Assessment of Microtia in Over 23 Million Consecutive United States Births. Issue 2 (March 2019) - Cabrejo, Raysa; Persing, John; Alperovich, Michael
Abstract : Purpose: Conflicting data exist regarding the incidence, demographics, and abnormalities associated with microtia. Using a large national cohort database, a comprehensive evaluation of microtia in the United States was performed. Methods: The Kids' Inpatient Database was reviewed over a 15-year consecutive period. Information regarding patient demographics, comorbidities, postoperative complications, and hospital setting was collected. Statistical tests were analyzed using independent t tests and χ 2 analysis. Results: A total of 23, 479, 792 births over 15 consecutive years from 1997 to 2012 were included in the study. Microtia was identified in 1563 births. Incidence of microtia was higher in males ( P <0.01) and patients of Asian or Hispanic race ( P <0.01). Patients with microtia had significantly more congenital anomalies relative to the rest of the population ( P <0.01). Specifically, cardiac and genitourinary anomalies were 51 and 19 times, respectively, more likely in microtia patients. Risk of associated congenital anomalies with microtia was highest in female and Black patients. 12.6% of all microtia patients had an associated craniofacial syndrome with a comparable postsurgical course to the nonsyndromic population. Conclusion: This study represents the largest national, longitudinal study of microtia allowing for demographic, socioeconomic, and comorbidity commentary. By quantifying relative risk of associated congenital anomalies, it can help inform the type and utility of screening modalities when evaluating microtia patients. Abstract : Supplemental Digital Content is available in the text